Predicting 30-Day Readmission Rate in Inflammatory Bowel Disease Patients: Performance of LACE Index. Issue 1 (19th June 2019) - George, Lauren A; Martin, Brendan; Gupta, Neil; Shastri, Nikhil; Venu, Mukund; Naik, Amar S
Abstract: Background and Aims: Readmission within 30 days in inflammatory bowel disease (IBD) patients increases treatment costs and serves as a quality indicator. The LACE (L ength of stay, A cuity of admission, C harlson comorbidity index, E mergency Department visits in past 6 months) index is used to predict the risk of unplanned readmission within 30 days. The aim of this study was to evaluate the accuracy of using the LACE index in IBD. Methods: Calculation of LACE index was done prospectively for IBD patients admitted to a single tertiary care center. Patient, disease, and treatment characteristics, as well as index hospitalization characteristics including indication for admission and disease activity measures were retrospectively recorded. Descriptive statistics and univariable exact logistic regression analyses were performed. Results: In total, 64 IBD patients were admitted during the study period. The 30-day readmission rate of IBD patients was 19% and overall median LACE index was 6, with IQR 6–7. LACE index categorized 16% of IBD patients in low-risk group, 82% in moderate risk group, and 2% in high-risk group. LACE index did not predict 30-day readmission (OR 1.35, CI: 0.88–2.18, P = 0.19). There was no significant difference in 30-day readmission rates with inpatient antibiotic or narcotic use, admission C-reactive protein (CRP), anemia, IBD duration, maintenance therapy, or prior IBD operation. For every 1 day increase in length of stay (LOS), patients were 8% more likely (OR: 1.08, 95% CI: 1.00–1.16) to be readmitted within 30 days ( P = .05). Conclusions: LACE index does not accurately identify 30-day readmission risk in the IBD population. As increased LOS is associated with higher risk, there may be benefit for targeted strategic resource allocation via specialized services. Lay Summary: Rate of readmission to the hospital after an admission is an important measure of quality care. Readmission rates for patients with inflammatory bowel diseases (IBDs) are high. This study examines whether a simple model designed to predict 30-day readmission rates in medical and surgery patients, called the LACE (L ength of stay, A cuity of admission, C harlson comorbidity index, E mergency Department visits in past 6 months) index, predicts readmission rates in patients with IBD. The conclusion is that the LACE index does not predict readmission rates in IBD. The hospital length in IBD patients was associated with more readmissions. IBD patients who have longer hospitalizations may benefit from additional support services to help prevent readmission to the hospital.